Safe and Simplified Salvage Technique for Exposed Implantable Cardiac Electronic Devices under Local Anesthesia - Jung, Chang Young (Arch Plast Surg, 2017)
BACKGROUND: Skin erosion is a dire complication of implantable cardiac pacemakers and defibrillators. Classical treatments involve removal of the entire generator and lead systems, however, these may result in fatal complications. In this study, we present our experience with a simplified salvage technique for exposed implantable cardiac electronic devices (ICEDs) without removing the implanted device, in an attempt to reduce the risks and complication rates associated with this condition. METHODS: The records of 10 patients who experienced direct ICED exposure between January 2012 and December 2015 were retrospectively reviewed. The following surgical procedure was performed in all patients: removal of skin erosion and capsule, creation of a new pocket at least 1.0–1.5 cm inferior to its original position, migration of the ICED to the new pocket, and insertion of closed-suction drainage. Patients with gross local sepsis or septicemia were excluded from this study. RESULTS: Seven patients had cardiac pacemakers and the other 3 had implantable cardiac defibrillators. The time from primary ICED placement to exposure ranged from 0.3 to 151 months (mean, 29 months. Postoperative follow-up in this series ranged from 8 to 31 months (mean follow-up, 22 months). Among the 10 patients, none presented with any signs of overt infection or cutaneous lesions, except 1 patient with hematoma on postoperative day 5. The hematoma was successfully treated by surgical removal and repositioning of the closed-suction drainage. CONCLUSIONS: Based on our experience, salvage of exposed ICEDs is possible without removing the device in selected patients.